Adults' facial impressions of children's niceness, but not shyness, show modest accuracy. Issue 12 (December 2020) - Collova, Jemma R; Sutherland, Clare AM; Jeffery, Linda; Bothe, Ellen; Rhodes, Gillian
Lay wisdom warns against "judging a book by its cover." However, facial first impressions influence people's behaviour towards others, so it is critical that we understand whether these impressions are at all accurate. Understanding impressions of children's faces is particularly important because these impressions can have social consequences during a crucial time of development. Here, we examined the accuracy of two traits that capture the most variance in impressions of children's faces, niceness and shyness. We collected face images and parental reports of actual niceness/shyness for 86 children (4–11 years old). Different images of the same person can lead to different impressions, and so we employed a novel approach by obtaining impressions from five images of each child. These images were ambient, representing the natural variability in faces. Adult strangers rated the faces for niceness (Study 1) or shyness (Study 2). Niceness impressions were modestly accurate for different images of the same child, regardless of whether these images were presented individually or simultaneously as a group. Shyness impressions were not accurate, for images presented either individually or as a group. Together, these results demonstrate modest accuracy in adults' impressions of niceness, but not shyness, from children's faces. Furthermore, our results reveal that this accuracy can be captured by images which contain natural face variability, and holds across different images of the same child's face. These results invite future research into the cues and causal mechanisms underlying this link between facial impressions of niceness and nice behaviour in children.